SUPERVISI KEPALA SEKOLAH DAN HUBUNGANNYA DENGAN PENGUASAAN KOMPETENSI GURU SMK - Deby Corina Putri; Burhanuddin Burhanuddin; Bambang Budi Wiyono (Universitas Negeri Malang, 2021)
Abstract: This research was conducted in order to know the level of supervising activities of the headmaster of State Vocational Schools in Malang City, the level of mastery of the competency of State Vocational School teachers in Malang, and the level of the relationship between the supervision of the headmaster and the mastery of State Vocational School teachers' competency in Malang. In this study the approach used is a quantitative approach and using a correlational research design. Based on the results of the analysis on the data obtained shows that the supervision activities of the headmaster of State Vocational Schools in Malang are included in the medium qualifications, the mastery of teacher competencies in the State Vocational Schools in Malang are included in the medium qualifications, and there is a positive and significant relationship between the supervision of the headmaster and the mastery of competencies State Vocational School teacher in Malang City. Keywords: supervision; mastery; competence Abstrak: Penelitian ini dilakukan agar dapat diketahui tingkat kegiatan supervis kepala sekolah SMK Negeri di Kota Malang, tingkat penguasaan kompetensi guru SMK Negeri di Kota Malang, dan tingkat hubungan supervisi kepala sekolah dengan penguasaan kompetensi guru SMK Negeri di Kota Malang. Pada penelitian ini pendekatan yang digunakan ialah pendekatan kuantitatif serta menggunakan desain penelitian korelasional. Berdasarkan hasil analisis pada data yang diperoleh menunjukkan bahwa kegiatan supervisi kepala sekolah SMK Negeri di Kota Malang termasuk dalam kualifikasi sedang, penguasaan kompetensi guru di SMK Negeri di Kota Malang termasuk dalam kualifikasi sedang, serta ada hubungan positif dan signifikan antara supervisi kepala sekolah dengan penguasaan kompetensi guru SMK Negeri di Kota Malang. Kata kunci: supervisi; penguasaan; kompetensi